Immune thrombocytopenic purpura in a child with Hodgkin's disease - Berberoğlu, Semha; Sarıalioğlu, Faik; Akyüz, Canan; Kutluk, Tezer; Büyükpamukçu, Münevver (The Turkish Journal of Pediatrics, 1995)
The occurrence of Immune thrombocytopenic purpura (ITP) in Hodgkin's disease is uncommon. This report describes a patient who developed ITP twice before splenectomy, and for the third time several years later, preceding an abdominal relapse of the disease. We suggest that patients with a history of Hodgkin's disease undergo diligent searches for active disease when ITP is diagnosed. ITP may be the only manifestation of active disease and may precede histologic documentation of Hodgkin's disease by months or years.
Keywords: Hodgkin's disease; immune thrombocytopenic purpura